Tradition and Identity in Nayantara Sahgal’s Novels: A Feminist Perspective: Exploring Gender Inequality and Empowerment in Nayantara Sahgal's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this male centric society woman is always dominated all over the world for centuries. All the religious books from all religions namely The Bible, The Quran and Manusmriti accept the role of woman with one voice as a being who lives in the “confines of the household”. But with the passage of time, awareness of education, science and with the help of social institutions, modern woman cried for freedom from the orthodox tradition. Now in 21th century we can see the sign of women’s emancipation. In India Men has taken the responsibility of women’s economic and social security. On the other hand, Indian woman play the role of ‘abla nari’.But now Indian woman is equal to man in every aspect.